Сільське господарство мешканців поселення Олександрівка 1 - Терпиловський, Р.В.; Горбаненко, С.А. (Археологія і давня історія України, 2010)
У статті підсумовано всі дані з сільського господарства, відомі з поселення київської культури Олександрівка 1 у Чернігівському Подесенні. З цією метою проаналізовано природні складові (екологія, палеоетноботаніка, археозоологія) і знаряддя праці. В статье подытожены все данные по сельскому хозяйству с поселения киевской культуры Александровка 1 в Черниговском Подесенье. С этой целью проанализированы природные составляющие (экология, палеоэтноботаника, археозоология) и орудия труда. Характеризуя сельское хозяйство в целом, следует признать его экстенсивным, таким, что неминуемо привело к истощению потенциальной ресурсной зоны памятника и дальнейшему переселению оттуда жителей на другие территории. All data on agriculture from the settlement of the kyiv culture of Oleksandrivka 1 in Chernihiv Desna Region, are summarized in the article. Natural constituents (ecology, palaeoethnobotany, archaeozoology) and tools are analysed. Characterizing agriculture on the whole, it is necessary to confess to his extensive, such, that unavoidable resulted in exhaustion of potential resource zone of settlement and further migration from there of habitants on other territories.